Analisis butir soal mata pelajaran ekonomi: Validitas, reliabilitas, tingkat kesukaran, dan daya pembeda - Dian Rachmawati; Andika Bayu Pradana (Jurnal Pendidikan Ekonomi (JUPE), 2025)
This study aims to improve the quality of assessment in economics subjects, particularly the topic of scarcity in grade X of high school. This study uses validity, reliability, difficulty level and discriminating power tests to analyze 25 previously developed questions. The test questions were conducted on 30 students of grade X of high school. From the results of the validity and reliability tests using SPSS 26, as many as 22 of the 25 questions (20 multiple choice and 5 essay) were declared valid and reliable. While the difficulty level test of the 25 questions is classified as easy, but from the calculation of the discriminating power of the questions, they have good quality to be used for assessment. From the test results, this study can be a reference for assessment tools in economics subjects, especially on the topic of scarcity in grade X of high school in Indonesia. However, further research is needed to improve the quality of the difficulty level of these questions.